2019
DOI: 10.1111/jgh.14634
|View full text |Cite
|
Sign up to set email alerts
|

N‐myc and STAT interactor correlates with severity and prognosis in acute‐on‐chronic liver failure of hepatitis B virus

Abstract: Background and Aim Hepatitis B virus‐related acute‐on‐chronic liver failure (HBV‐ACLF) is characterized by acute deterioration of chronic liver disease with excessive inflammation. N‐myc and STAT interactor (NMI), an inflammation‐mediated protein, involves in various inflammatory‐related diseases, but the role of NMI in development and prognosis in HBV‐ACLF remains to be elucidated. Methods Serum NMI from healthy controls (HCs, n = 20), chronic hepatitis B (CHB, n = 50) patients, and HBV‐ACLF patients (n = 50)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Wu et al showed that NMI expression in human lung A549 cells was upregulated after H3N2 SIV infection [40]. NMI levels also elevated in serum and liver tissue of patients with hepatitis B virus-related acute-tochronic liver failure and the concentrations of NMI decreased when in convalescent stage of disease [19]. Our current results showed that the expression of NMI in both serum and BALF was signi cantly increased in CAP and that NMI levels were positively correlated with mortality and ICU admission.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Wu et al showed that NMI expression in human lung A549 cells was upregulated after H3N2 SIV infection [40]. NMI levels also elevated in serum and liver tissue of patients with hepatitis B virus-related acute-tochronic liver failure and the concentrations of NMI decreased when in convalescent stage of disease [19]. Our current results showed that the expression of NMI in both serum and BALF was signi cantly increased in CAP and that NMI levels were positively correlated with mortality and ICU admission.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies have already shown that NMI is associated with various in ammatory diseases [18,19,39,40].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Enriched genes such as A2M [ Chen et al, 2010 ], CLEC5A [ Teng et al, 2016 ], ZBP1 [ T. Zhang et al, 2020 ], PLSCR1 [ Luo et al, 2018 ], FKBP5 [ Hao et al, 2020 ], FPR2 [ Schloer et al, 2019 ], CD226 [ Redlberger-Fritz et al, 2019 ], PTPN22 [ Crabtree et al, 2016 ], CEACAM1 [ Ye et al, 2018 ], CD80 [ Lumsden et al, 2000 ] CD86 [ Lumsden et al, 2000 ], CD68 [ McGuinness et al, 2000 ], MLKL (mixed lineage kinase domain like pseudokinase) [ Gaba et al, 2019 ] and TRIM28 [ Krischuns et al, 2018 ] were liable for progression of influenza viral infection, but these genes may be associated with development of SARS-CoV-2 infection. Enriched genes such as LILRB2 [ Alaoui et al, 2018 ], SERPINB9 [ Mangan et al, 2017 ], FCGR3A [ Poonia et al, 2010 ], MICB (MHC class I polypeptide-related sequence B) [ Libraty et al, 2014 ], CD274 [ Jeong et al, 2008 ], SLAMF7 [ O'Connell et al, 2019 ], CMPK2 [ El-Diwany et al, 2018 ], IFIT5 [ Rohaim et al, 2018 ], APOBEC3A [ Berger et al, 2011 ], APOBEC3F [ Burdick et al, 2013 ], HAVCR2 [ Sironi et al, 2014 ], NMI (N-myc and STAT interactor) [ Xiong et al, 2019 ], CD96 [ Eriksson et al, 2012 ], CLEC2D [ Varaden et al, 2019 ], CD53 [ Tippett et al, 2013 ] and CD69 [ Yong et al, 2017 ] were linked with progression of various viral infections, but these genes may be key for progression of SARS-CoV-2 infection. Enriched genes such as CD209 [ Amraei et al, 2020 ], APOL1 [ Wu et al, 2020 ], PARP14 [ Webb and Saad, 2020 ], TF (transferrin) [ McLaughlin et al, 2020 ], ACE2 [ Yan et al, 2020 ], FLT1 [ Giardini et al, 2020 ] and BRCA2 [ Singh and Bharara Singh, 2020 ] were involved in advancement of SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Even though several biomarkers such as microRNA (hsa-miR-21-5p), the inflammation-mediated protein (N-myc and ATAT interactor, NMI) may be useful novel biomarkers of ACLF ( Ding et al, 2015 ; Xiong et al, 2019 ), more appropriate, accurate, and early indicators are still needed owing to the rapid progression of ACLF. It is well known that ALCF patients have higher complexity and diversity within the BCP/PC region of HBV, indicating distinct quasispecies characteristics among ALCF patients ( Chen L. et al, 2013 ).…”
Section: Emerging Early Indicators Of Aclf and Potential Therapy Targmentioning
confidence: 99%